2004
DOI: 10.1890/04-0005
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships Among Inbreeding, Herbivory, and Disease on Reproduction in a Wild Gourd

Abstract: Because inbreeding, herbivory, and disease are common in plants and their separate impacts on fitness are well documented, investigators have begun to examine the consequences of inbreeding on plant-herbivore and plant-pathogen interactions. In this study, we examined the interrelationships among inbreeding, herbivory, and disease on reproductive output through both male (pollen production and pollen performance) and female (fruit and seed production and seed germination) functions. Inbred (selfed) and outbred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
112
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(123 citation statements)
references
References 76 publications
(77 reference statements)
10
112
1
Order By: Relevance
“…6,7 Compared to outbred plants, inbred plants are more susceptible to herbivores -under both field and lab conditions, [8][9][10] and herbivores perform better when they feed on inbred plants. [11][12][13] Previous studies using horsenettle (Solanum carolinense L.), a perennial weed native to the United States, showed that tobacco hornworm caterpillars (Manduca sexta L.) preferred to feed on inbred plants more than outbreds.…”
Section: Inbreeding Compromises Host Plant Defense Gene Expression Anmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Compared to outbred plants, inbred plants are more susceptible to herbivores -under both field and lab conditions, [8][9][10] and herbivores perform better when they feed on inbred plants. [11][12][13] Previous studies using horsenettle (Solanum carolinense L.), a perennial weed native to the United States, showed that tobacco hornworm caterpillars (Manduca sexta L.) preferred to feed on inbred plants more than outbreds.…”
Section: Inbreeding Compromises Host Plant Defense Gene Expression Anmentioning
confidence: 99%
“…14 Inbreeding in horsenettle causes significant reductions in the plant's induced defense responses 18,23 and resistance to herbivory. [8][9][10] We used only minimal manipulation, a single generation of host plant inbreeding, to produce differences (inbred vs. outbred) in the host plants of an indigenous plant-insect system (horsenettle-tobacco hornworm). Our findings provide further evidence that plant inbreeding can produce biochemical changes in host plants that can impact the health and vigor of animals at a higher trophic level.…”
Section: Inbreeding Compromises Host Plant Defense Gene Expression Anmentioning
confidence: 99%
“…Kuntze, but response was more variable in selfing populations (Hoebe et al 2011). Herbivory has been shown to magnify inbreeding depression Stephenson et al 2004;Leimu et al 2008) as well as outbreeding depression (Leimu and Fischer 2010). Indeed, antagonists have frequently been implied as a selective force favouring outcrossing in plants (Levin 1975;Busch 2004).…”
Section: Introductionmentioning
confidence: 99%
“…inbreeding depression). Although investigators have only recently begun to document the impacts of inbreeding on plant -insect interactions, several recent studies show that inbred plants suffer higher levels of herbivory than outbred plants [24,25], and that herbivores develop more rapidly on inbred plants [26,27]. The mechanisms underlying such effects are not well studied, but may include indirect effects mediated by a general reduction in vigour associated with inbreeding [23,24,28], as well as the direct disruption of plant defences-for example, through the effects of deleterious recessives on the expression of genes involved in plant defence pathways [29,30].…”
Section: Introductionmentioning
confidence: 99%